Revision on Renal Sympathetic Ablation in the Treatment of Resistant Hypertension - Filipa Saraiva, Ana (Current Hypertension Reviews, 2016)
Introduction: Hypertension is one of the most prevalent diseases in the world, with about 1 billion people affected and a possible increase to 1.5 billion by 2025. Despite advances in treatment, a proportion of patients remain resistant to conventional treatment and uncontrolled, and this can adversely affect future cardiovascular events and mortality. This alarming growth is already reflected in an important public health problem and one of the largest economic burdens of health, requiring new approaches and development of different strategies to fight this problem. Objectives: This review will focus on the definition of resistant hypertension and its etiology, as well as in contemporary evidence supporting the usefulness of renal sympathetic denervation while addressing current and emerging devices, potential treatment indications in the future and unresolved issues that need to be addressed before renal sympathetic denervation can be adopted not only as a last resort exclusively for resistant hypertension. Finally an evaluation algorithm for patients with resistant hypertension which should be implemented before the execution of this technique will be proposed. Results: Renal sympathetic denervation is a technique that possibly could have future implications in the population with hypertension, especially those with true resistant hypertension. This technique aims to reduce the renal sympathetic activation (a component in the pathophysiology of hypertension) through the destruction of the renal sympathetic nerves located in the adventitia of the renal arteries. There are several catheters that can be used; each with its specifications and therefore their selection should be made individually depending on the profile of the patient. However, a detailed pre-procedure evaluation is extremely important to exclude the large percentage of individuals with uncontrolled hypertension due to several factors that make it impossible to control blood pressure, but are likely to be corrected and as such should be treated first. Conclusion: Several studies have demonstrated the efficacy and safety both in resistant hypertension as in other co-morbidities. However, there is no marker to evaluate the effectiveness of this technique, neither a robust predictor of a stronger response in certain patients. Additionally there are several factors that seem to influence various parameters related to this technique. Therefore there is a need for additional studies to consolidate the data existing on the renal sympathetic denervation.
Keywords: resistant hypertension